Effect of Ultrasound on the Stability of Turmeric Oleoresin Microencapsulated in Gelatin-Collagen Matrices - Zuanon, Larissa A. C. [UNESP]; Malacrida, Cassia R. [UNESP]; Telis, Vania R. N. [UNESP] (Wiley-Blackwell, 2017)
This study evaluated the effect of sonication on the stability of turmeric oleoresin microcapsules produced by spray and freeze-drying using blends of gelatin-collagen as encapsulating matrices. Samples prepared with different wall matrix formulations presented solubility between 82.7 and 86.9%, yield above 88% and encapsulation efficiency between 17.41 and 56.21%. The wall matrix composed of 2% gelatin and 28% collagen (C2G28), which presented the highest yield (94.7%) and good encapsulation efficiency (42.83%), was adopted to investigate the effects of ultrasound in the emulsification step (C2G28US), to compare the performance of spray and freeze-drying, as well as to study stability of the microcapsules during storage under incident light. Ultrasound combined with spray drying resulted in the smallest particle size, according to SEM analyses and the highest curcumin retention (342.84mg/g). Sonication also showed positive effects on product stability, with better curcumin color retention observed for spray-dried microcapsules. Practical ApplicationsEncapsulation of turmeric oleoresin by spray drying in protein matrices composed of gelatin and collagen hydrolysate was enhanced by using ultrasound in the emulsification step, which resulted in the smallest particle size, higher curcumin retention and greater color stability under light incidence. The produced curcumin capsules may be used as a food supplement or as a natural dye.